2009
DOI: 10.2353/ajpath.2009.080676
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Gene Expression Analysis of Tumor-Associated Macrophages from Mouse Mammary Tumors

Abstract: Clinical and experimental evidence indicates that tumor-associated macrophages (TAMs) promote malignant progression. In breast cancer, TAMs enhance tumor angiogenesis, tumor cell invasion, matrix remodeling, and immune suppression against the tumor. In this study, we examined late-stage mammary tumors from a transgenic mouse model of breast cancer. We used flow cytometry under conditions that minimized gene expression changes to isolate a rigorously defined TAM population previously shown to be associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
198
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(202 citation statements)
references
References 71 publications
4
198
0
Order By: Relevance
“…For example, TAMs recruited to hypoxic areas are likely to then be usurped to promote tumour angiogenesis 41 , whereas TAMs at the tumour-stroma interface play an active part in invasion and angiogenesis 42 . Transcriptome profiling of freshly isolated TAMs also suggests that they are similar to those that are involved in development 43 .…”
Section: Tumour-associated Macrophagesmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, TAMs recruited to hypoxic areas are likely to then be usurped to promote tumour angiogenesis 41 , whereas TAMs at the tumour-stroma interface play an active part in invasion and angiogenesis 42 . Transcriptome profiling of freshly isolated TAMs also suggests that they are similar to those that are involved in development 43 .…”
Section: Tumour-associated Macrophagesmentioning
confidence: 94%
“…For example, TAMs recruited to hypoxic areas are likely to then be usurped to promote tumour angiogenesis 41 , whereas TAMs at the tumour-stroma interface play an active part in invasion and angiogenesis 42 . Transcriptome profiling of freshly isolated TAMs also suggests that they are similar to those that are involved in development 43 .Most of the studies that have demonstrated a crucial role for macrophages in regulating tumour progression have either used genetic manipulation, such as Csf1 op/op mice, which are deficient in the macrophage growth factor colony stimulating factor 1 (CSF1), or pharmacological depletion, such as clodronate-liposome treatment, which causes selective killing of macrophages. These approaches resulted in a substantial decrease in macrophage infiltration into the tumour, which led to inhibition of tumour angiogenesis, tumour growth and metastasis in different animal models 33,[44][45][46][47] .…”
mentioning
confidence: 99%
“…15 However, recent gene profiling experiments revealed that TAMs often share features of both types, albeit with a shift to this immunoregulatory type. 16,17 The prognostic value of TAMs in NSCLC has been evaluated in patients who have undergone surgery. Chen et al reported that the density of TAMs negatively correlates with patient survival, which is associated with tumor angiogenesis 18 and promotion of tumor invasiveness and matrix-degrading activity.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages that infiltrate tumor tissues, also termed tumor-associated macrophages (TAMs), can be driven by tumor-derived and T-cell-derived cytokines to acquire such a polarized phenotype, and have a key role in subversion of adaptive immunity and in inflammatory circuits that promote tumor growth and progression [7]. Fully polarized M1 and M2 macrophages are the extremes of a continuum of functional states; in contrast to this binary M1/M2 definition, there are several other distinct populations that share features of both types [8]. Functions of these subpopulations in tumor progression need careful elucidation.…”
Section: Introductionmentioning
confidence: 99%